2016
DOI: 10.1371/journal.pone.0153948
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Motor Unit Number Index (MUNIX) Measurements in 6 Muscles in a Single-Subject “Round-Robin” Setup

Abstract: BackgroundMotor Unit Number Index (MUNIX) is a neurophysiological measure that provides an index of the number of lower motor neurons in a muscle. Its performance across centres in healthy subjects and patients with Amyotrophic Lateral Sclerosis (ALS) has been established, but inter-rater variability between multiple raters in one single subject has not been investigated.ObjectiveTo assess reliability in a set of 6 muscles in a single subject among 12 examiners (6 experienced with MUNIX, 6 less experienced) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 21 publications
11
38
0
Order By: Relevance
“…However, the repeatability of MUNIX under repeatability conditions has rarely received sufficient attention. In one study, a “round-robin” setup was performed (Neuwirth et al, 2016), in which twelve raters made two MUNIX measurements of six muscles on the same subject in two sessions separated by one day. A considerate amount of intra-rater coefficient of variance was reported (mean 14.1 ± 4.3%, range 6.6 – 22.9%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the repeatability of MUNIX under repeatability conditions has rarely received sufficient attention. In one study, a “round-robin” setup was performed (Neuwirth et al, 2016), in which twelve raters made two MUNIX measurements of six muscles on the same subject in two sessions separated by one day. A considerate amount of intra-rater coefficient of variance was reported (mean 14.1 ± 4.3%, range 6.6 – 22.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The research protocol was approved by the local ethic committee. The biceps brachii muscle was selected as it was considered one most challenging muscle for MUNIX calculation according to Neuwirth et al (2016). The experimental setup was configured following a previous study (Peng et al, 2016), as shown in Figure 1(a), to record the isometric contraction of the biceps brachii during flexion, while spurious force contributions from other muscles were minimized with the application of a fiberglass cast.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPS has good reproducibility based on the test-retest coefficient of variation (COV) in healthy subjects (COV = 10.4%) (Wang and Delwaide, 1995), and is even higher in amyotrophic lateral sclerosis (ALS) patients where the number of MU is reduced (COV = 4%) (Wang and Delwaide, 1998). A good within raters COV (between 5.8 and 9%) and between raters COV (between 13.5 and 16.4%) is also found when MUNIX is applied to abductor pollicis brevis muscle of healthy subjects (Neuwirth et al, 2016). MUNIX and AMPS were widely used in clinical studies, particularly to document the motor unit loss which characterized ALS (Wang and Delwaide, 1998;Wang et al, 2002Wang et al, , 2009Nandedkar et al, 2010;Boekestein et al, 2012;Furtula et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related loss of motor neurons is a major component of sarcopenia and muscle mass loss [9], which results in a decrease in muscle function caused by disuse. The Motor Unit Number Index (MUNIX) is a neurophysiological measure that provides an index of the number of lower motor neurons in a muscle using the compound muscle action and surface electromyographic interference pattern [15]. Weaker individuals exhibit a smaller motor unit number index (MUNIX) value [9, 16].…”
Section: Muscle Mass Lossmentioning
confidence: 99%